2017
DOI: 10.1111/ibi.12511
|View full text |Cite
|
Sign up to set email alerts
|

A revision of species limits in Neotropical pipits Anthus based on multilocus genetic and vocal data

Abstract: Previous investigations of the systematics of Neotropical pipits Anthus revealed multiple cases of paraphyly. We revised the species limits of this group based on sequence data of mitochondrial (ND2) and nuclear genes (ACOI9, MB, FGB5) from 39 tissue samples of all 22 subspecies‐level taxa in the New World Anthus clade, as well as analysis of display song. We found that Anthus lutescens peruvianus is not part of Yellowish Pipit Anthus lutescens genetically or vocally; thus, we elevate peruvianus to species ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
2
14
1
2
Order By: Relevance
“…However, the monophyly of B is poorly supported and did not show a structured pattern of geographic differentiation congruent with current morphology-based taxonomy of A. correndera . We found A. antarcticus to be embedded within the lowlands clade, and unlike what was reported by Voelker (1999) and Van Els & Norambuena (2018) in their analyses of the Anthus genera, this species seems not closer to correndera or grayi than to chilensis - catamarcae . Unfortunately, the low sample sizes of some of the subspecies/regions could result in the low resolution of clade B.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…However, the monophyly of B is poorly supported and did not show a structured pattern of geographic differentiation congruent with current morphology-based taxonomy of A. correndera . We found A. antarcticus to be embedded within the lowlands clade, and unlike what was reported by Voelker (1999) and Van Els & Norambuena (2018) in their analyses of the Anthus genera, this species seems not closer to correndera or grayi than to chilensis - catamarcae . Unfortunately, the low sample sizes of some of the subspecies/regions could result in the low resolution of clade B.…”
Section: Discussioncontrasting
confidence: 83%
“…Although A. antarcticus is phenotypically clearly different from A. correndera , with a streaked, dark appearance and bigger size ( Tyler, 2004 ), it has been suggested that this taxon could have differentiated after South Georgia was colonized by specimens of A. correndera ( Tyler, 2004 ). However, recent information based on a multilocus analysis, suggests that A. correndera is a species complex, with A. c. catamarcae sister to A. c. calcaratus , A. c. correndera sister to A. c. chilensis and A. c. grayi sister to the species A. antarcticus, which is nested within this complex ( Van Els & Norambuena, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This code will create a (temporary) BEAST2 configuration file, from the FASTA file with name anthus_aco.fas (which is supplied with the package, from Van Els & Norambuena, ), using the same default settings as BEAUti, which are, among others, a Jukes‐Cantor site model, a strict clock, and a Yule birth tree prior. babette will then execute BEAST2 using that file, and parses the output.…”
Section: Usagementioning
confidence: 99%
“…This code will create a (temporary) BEAST2 configuration file, from the FASTA file with name anthus_aco.fas (which is supplied with the package, from (Van Els & Norambuena 2018)), using the same default settings as BEAUti, which are, among others, a Jukes-Cantor site model, a strict clock, and a Yule birth tree prior. will then execute BEAST2 using that file, and parses the output.…”
Section: Usagementioning
confidence: 99%